Enterpreneurial Motivation Students Reviewed from Adversity Quotient and Type A and B Personality - Mliwes Hardhadhedhali; Suparmi Suparmi (Universitas Katolik Soegijapranata, 2019)
This study aims to determine empirically the correlation of adversity quotient with entrepreneurial motivation, and the differences in entrepreneurial motivation between students with type A and type B personality. The hypotheses in this study are: (1) there is a positive relationship between adversity quotient and entrepreneurial motivation; (2) there are differences in entrepreneurial motivation in students with types A and type B personality, entrepreneurial motivation in students with type A personality is higher than students with type B personality. The quantitative methodology is used for this study. Subjects in this study were 96 students of Soegijapranata Catholic University who were taking theses selected based on incidental sampling technique. In this research, the scales are used as data collection methodology, they are Entrepreneurial Motivation Scale, Adversity Quotient Scale and Type A and B Personality Scale. The data obtained are then analyzed by Product Moment correlation and t-test techniques. The result of hypothesis testing (1) shows rxy = 0,375 with p equal to 0,000 (p < 0.01) then the hypothesis is accepted. Hypothesis testing (2) shows the value of t = 2,768 with p at 0,007 (p < 0.01) then the hypothesis is also accepted.